Retrospective climate predictions for the 2015 US wind drought ... - Bellprat, Omar; Lledó, Llorenç (https://b2share.eudat.eu, 2018)
This dataset contains monthly means of surface wind speed, precipitation and geopotential height at 500 and 200 hPa for 4 AGCM experiments that simulate the first three months of 2015. The experiments were performed with the EC-Earth forecast system, using only the atmospheric component (IFS), and forcing the SST and sea ice boundary conditions from ERA-Interim reanalysis. The initial conditions are also from ERA-Interim. The four experiments are: INI: the SSTs are forced from daily observed values. 100 members. CLIMSST: the SSTs are forced from a daily climatology of the 1981-2010 period. 100 members. TROP: the SSTs are forced from daily observed values in the tropics (10S to 10N), from the climatology above/below 15N/S and a transition zone in between. 100 members. HIND contains a Hindcast for the 1981-2010 with 10 members and the INI configuration. ...